A Study on Nψβ and Nβψ - Closed sets in Neutrosophic Topological spaces (Baghdad Science Journal, 2023)
The aim of this paper is to introduce the concept of N  and Nβ -closed sets in terms of neutrosophic topological spaces. Some of its properties are also discussed.